Outcomes after percutaneous coronary intervention (PCI) in patients with prior coronary artery bypass grafting (cabg). (14th October 2021) - Cohen, N S; Dinh, D; Ajani, A; Clark, D; Brennan, A; Nan Tie, E; Dagan, M; Hamilton, G; Sebastian, M; Shaw, J; Oqueli, E; Freeman, M; et al.
Abstract: Background: In patients with prior CABG requiring subsequent PCI there is uncertainty whether bypass grafts or native coronary arteries should be targeted. Methods: We analysed data from 2, 764 patients with prior CABG in the Melbourne Interventional Group registry (2005–2018), divided into two groups: those undergoing PCI to a native vessel (n=1, 928) and those with PCI to a graft vessel (n=836). Results: Patients with a graft vessel PCI were older, had more high-risk clinical characteristics (prior MI, heart failure, ejection fraction <50%, renal impairment, peripheral and cerebrovascular disease), and high-risk procedural features (ACC/AHA types B2/C lesions). However, patients in the native vessel group were more likely to have PCI to a chronic total occlusion. The majority of graft PCI were to saphenous vein grafts (84%), with 10% to radial and 6% to LIMA/RIMA grafts. Distal embolic protection devices were used in 30% of graft PCI. Patients with graft PCI had higher rates of no reflow (6.3% vs. 1.5%; p<0.001), coronary perforation (p=0.016) and inpatient stent thrombosis (p=0.028). However, 30-day mortality and major adverse cardiovascular and cerebrovascular events (MACCE) were similar. Unadjusted long-term mortality (median follow up 4.8 years) was higher in patients who had undergone a graft PCI (44% vs. 32%, p<0.001), but following Cox proportional hazards modelling, PCI vessel type was not a predictor of long-term mortality (HR 1.13; 95% CI 0.96–1.33, p=0.14). Conclusions: Early clinical outcomes and risk-adjusted long-term mortality are similar for patients with prior CABG undergoing PCI to a native vessel or a bypass graft. Funding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): The Alfred Hospital